Aspect-Oriented Product Family Modeling - Zhang, Qinglei (My University, 2013)
The set of related products is referred to as a product family, and feature-modeling is a widely used technique to capture the commonalities and variabilities of a product family in terms of "features". With the growing complexity of software product families in several software industries, the development, maintenance and evolution of complex and large feature models are among the main challenges faced by feature-modeling practitioners. In particular, more sophisticated feature-modeling techniques are required to address the problems caused by unanticipated changes and crosscutting concerns in feature models.
This thesis tackles the above challenges in feature-modeling by adopting the aspect-oriented paradigm at the feature-modeling level. I first introduce a specification language, called AO-PFA, which is an extension of the Product Family Algebra (PFA) language. I then proposed a formal verification technique to check the compatibility of aspects with their base specifications in AO-PFA. In the aspect-oriented paradigm, the process of combining aspects with base specifications is referred to as the weaving process. I finally discussed how to perform the weaving process in AO-PFA. By proposing a systematic approach to extend product family algebra with the abilities of specifying, verifying, and weaving aspects, we are able to handle the difficulties that arise from crosscutting concerns and unanticipated changes in large-scale feature models.
Keywords: Aspect-Oriented Paradigm; Feature Modeling; Product Family Algebra; Formal Methods; Other Computer Engineering; Other Computer Engineering